Telang Flower Infusion Reduces Inflammation and Increases Goblet Cells in Infection Salmonella typhimurium Models - Rian Anggia Destiawan; Delvia Asista Indarusanti; Ahdiah Imroatul Muflihah; Anas Fadli Wijaya (Jurnal Kesehatan dr. Soebandi, 2025)
Typhoid fever is an infectious disease caused by Salmonella Sp. This infection leads to a rise in inflammatory cells and a reduction in goblet cells, which are essential for protecting the intestinal lining. An alternative treatment option is the use of telang flower infusion, as its antioxidant content and active compounds show potential as anti-inflammatory agents. The purpose of this study was determining the effect of telang flower infusa on reducing inflammatory cells and increasing goblet cells in mice infected with S. typhimurium. This research design used the complete Randomized Design Method (RAL). The population of this study used mice (Mus musculus) which were divided into 6 groups: negative (without treatment), positive (only infected), stimuno (given a dose of 0.25 ml/20 g BB), treatment 1 (given telang flower infusa dose 0.25 ml/20 g BB), treatment 2 (given telang flower infusa dose 0.5 ml/20 g BB), and treatment 3 (given telang flower infusa dose 1 ml/20 g BB). Then, followed by necropsy, tissue processing, histology observation, and data analysis using Kruskal Wallis. Based on data analysis using normality and homogeneity test, the sig value was <0.05. So, the data is non-normal and not homogeneous. Meanwhile, in the Kruskal Wallis test, the sig value was 0.288 > 0.05, which means that there is no effect of swallowed flower infusion. There is no effect of telang flower infusa on reducing inflammatory cells and increasing goblet cells. Biologically, telang flower infusion can reduce inflammatory cells and increase goblet cells in mice infected with Salmonella typhimurium infection